The latent tuberculosis infection cascade of care in Iqaluit, Nunavut, 2012–2016 - Christopher Pease; Alice Zwerling; Ranjeeta Mallick; Mike Patterson; Patricia Demaio; Sandy Finn; Jean Allen; Deborah Van Dyk; Gonzalo G. Alvarez (BMC Infectious Diseases, 2019)
Abstract Background A remote arctic region of Canada predominantly populated by Inuit with the country’s highest incidence of tuberculosis. Methods The study was undertaken to describe the latent tuberculosis infection (LTBI) cascade of care and identify factors associated with non-initiation and non-completion of LTBI treatment. Data were extracted retrospectively from medical records for all patients with a tuberculin skin test (TST) implanted in Iqaluit, Nunavut between January 2012 and March 2016. Associations between demographic and clinical factors and both treatment non-initiation among and treatment non-completion were identified using log binomial regression models where convergence could be obtained and Poisson models with robust error variance where convergence was not obtained. Results Of 2303 patients tested, 439 (19.1%) were diagnosed with LTBI. Treatment was offered to 328 patients, was initiated by 246 (75.0% of those offered) and was completed by 186 (75.6% of initiators). In multivariable analysis, older age (adjust risk ratio [aRR] 1.17 per 5-year increase, 95%CI:1.09–1.26) and undergoing TST due to employment screening (aRR 1.63, 95%CI:1.00–2.65, compared to following tuberculosis exposure) were associated with increased non-initiation of treatment. Older age (aRR 1.13, 95%CI: 1.03–1.17, per 5-year increase) was associated with increased non-completion of treatment. Conclusions A similar rate of treatment initiation and higher rate of treatment completion were found compared to previous North American studies. Interventions targeting older individuals and those identified via employment screening may be considered to help to address the largest losses in the cascade of care.